Alex, approximately - Bennett, Jenn (Simon Pulse, an imprint of Simon & Schuster Children's Publishing Division, 2017)
Seventeen-year-old Bailey moves to California to live with her father and, perhaps, finally meet an online friend and fellow film buff, but soon finds herself attracted to an annoying co-worker.